Analysis of Higyene Food Sanitation in Public Hospital in Sultan Iskandar Muda Regency Nagan Raya - Jun Musnadi Is; Liza Sartika; Zakiyuddin Zakiyuddin (Journal of Nutrition Science, 2020)
Introduction on food sanitation hygiene is an effort to control the factors of food, people, places and equipment that can or may cause illness or health problems. The purpose of this research is to find out how the Analysis of Food Sanitation Hygiene at Sultan Iskandar Muda Regional General Hospital, Nagan Raya Regency. This research is a qualitative study conducted at Sultan Iskandar Muda Regional General Hospital, Nagan Raya Regency, when the research was conducted in January 2019. Research informants as many as 12 people namely, 9 food handlers, 1 program implementer, and 2 patients, taken by purposive sampling. The results showed the overall results of food sanitation hygiene, especially in the room, were quite good because they had storage, cooking and serving food, but still had water deposits because they did not have slope / slope so the floor was slippery, infrastructure was inadequate because of the aids used, PPE that has not been well used, the food is counted pretty good because the storage is separate but certainly not contaminated because the food served is sometimes in direct contact with hands, and HR food handlers are inadequate because each sift consists of three people who process, serve and deliver food. Conclusion sanitation hygiene has been counted as good, however it is necessary to make improvements to be declared good overall. It is recommended to the officers in charge of the hospital to pay more attention to sanitary hygiene, both food and others.